Traditional Art Strategy in Responding Capitalization: Case Study of Kubrosiswo Cultural Art Commodification - Irianto, Agus Maladi; Laksono, Arido; Hermintoyo, Hermintoyo (Harmonia: Journal of Arts Research and Education, 2018)
The aim of this study is to describe traditional art capitalization as the cultural identity of a society and a strategy of the society which supports traditional art in developing cultural comodification in line with the demands of the tourism industry. The paper is based on field research presenting a case study of the existence of Kubrosiswo traditional art from Magelang Regency, Central Java, Indonesia which develops the cultural comodification as a strategy to respond to the economic capitalization demands, especially the emergence of the tourism industry which appeared in this globalization era. One alternative strategy which is developed in this research is by making a documentary film. The documentary film is one of the strategies to present the reality based on the description in the field, and it is also expected to create awareness in recognizing and comprehending the knowledge of Kubrosiswo traditional art.